Strategi Pengembangan Usaha Pada Butik Keika (Studi Pada Butik Keika Jl. Tb. Simatupang Ruko Komplek Palm Mas No. 119 ii Medan) - Dwi Ayu Arsita Sari (Jurnal Niaga & Bisnis (e-journal), 2015)
The purpose of this study was to determine internal strengths and weaknesses boutique in achieving goals and external factors into the opportunities and threats that affect the activity and determine Keika boutique business development strategies that can be run at Boutique Keika Jl . Tb Simatupang Commercial Complex No. Palm Mas . 119 ii field . In this study, the method used is descriptive method with qualitative data . Data were obtained from observations , interviews and literature study . Informants in this study were divided into two groups , namely the determination of key informant informant using purposive sampling is Keika boutique owners and key informants using accidental sampling , namely consumers and customers Keika boutiques . Based       on        theresults         of research conductedin the fieldindicatethatKeikaBoutiquehas a strategytoexpand its business. Analysis usingthe SWOTmatrixproducesomestrategiesthatcan be runboutiquekeikatoexpand its businessthatimprovecustomercomfort, improve product qualityandcustomerservice, createnew productsespeciallywomen's clothingthat ismore variedandinnovative, improve knowledgeaboutconsumer appetite forfashion products, Increase the number ofemployees soemployees canwork optimally, makinga member cardtoapply theterms and conditionswhich can beused by consumers toget discounts, maintaininggood relationshipswithsuppliers tomaintain product qualityandimprove andadd to thepromotional activities.